The Effect of Using Task-Based Language Learning On the Students’ Speaking Achievement at Senior High School - Prenata Mulia Sari (Faculty of Education, 2024)
Speaking is one of the English skills that is important for students to learn and speaking ability should be owned by students as a medium of communication in the class with the teacher and their friends. Nevertheless, speaking is rarely practised in primary and secondary English classes. Most students must still practice speaking English (Ataeifar et al., 2019). This is because speaking in most classrooms is mainly done by the teachers, who are deemed to be the authority of the school, and learners have no opportunity to exercise their language abilities and find it difficult to express their abilities and thoughts in English (Al-Sohbani, 2013). In this case, the role of the English teacher is essential in using the appropriate teaching approach for speaking so that the students can practice speaking English as a communication medium. Many teaching techniques can be used to teach speaking to give the students practice speaking English. One teaching technique that can be used in speaking is Task-based Language Learning. Task-based Language Learning consists of activities and tasks that help language learners communicate effectively in the target language. The main goal of Task-based Language Learning is to engage learners in actual language use by performing a series of tasks, while interacting with other learners (Ellis, 2003). Task-based learning has been used as a technique to help students achieve speaking achievement. Former researchers conducted many studies about the effect of the Task-based Language Learningّonّstudents’ّspeakingّachievement.ّMeanwhile, the previous studies on the effect of Task-basedّ Languageّ Learningّ onّ theّ students’ّ speakingّ achievementّ in senior high school remained unexplored. That is why, the present research tried to fill the gap by exploring Indonesian senior high school students' speaking achievement in the Merdeka Curriculum to know the significant effect of the Task-based Language Learning approach onّ theّ students’ّ speakingّ achievement at senior high school. This research aimed to know the effect of Task-basedّLanguageّLearningّonّtheّstudents’ّ speaking achievement in senior high school. I conducted this research at one of the senior high schools in Jember using a quasi-experimental research design to determine whether or not the Task-based Language Learning approach affects the speaking achievement of tenth graders. This research involved 72 participants of senior high school students. The data were collected through speaking post-task and then statistically analyzed using an independent sample t-test. The analysis of the data gained from the speaking post-test showed no significant effect of using the Task-based Language Learning on the students' speaking achievement at senior high school. This means the experimental group, taught to speak using task-based language learning, did not affect their speaking achievement. The researcher predicted that it was related to the absence of the pre-testّstageّwhereّtheّresearcherّcouldّnotّestimateّtheّparticipants’ّEnglishّ proficiency level. In addition, Klepper (2003) stated that Task-based Language Learning is not suitable for EFL students because it fails to provide adequate linguistic support (i.e. the main focus is on task completion and EFL students do not have sufficient linguistic proficiency to engage in open-ended communicative tasks). Another factor affecting the research results could be related to the area of the school that is remote area. Therefore, they tended to use local language or Bahasa Indonesia rather than English. The students avoid using English as a means of communication used in the classroom. Moreover, it was difficult for the researcher to control the use of English in the class by the students since there were 36 students in the class. The classes with a large number of students are also a cause for concern (Jeon & Hahn, 2006). Additionally, the class had limited time available to complete assignments and all other activities in Task-based Language Learning cycle. The researcher needed to adjust the tasks given in the learning time because the researcher often ran out of time when carrying out the treatments in the experimental class which could effect less optimal result. Not only the researcher, the students also experienced the same thing. The students who were not accustomed to using Task based Language Learning approach spent a long time doing their tasks. Then, based on the researcher's experience, the researcher predicted that there was no significant effect made by the experimental group and the control group because the experimental group learnt and performed a series of tasks with their partner or their group while the control group learnt and performed the learning result with any language form and structure they wanted
The Effect of Using Task-Based Language Learning On the Students’ Speaking Achievement at Senior High School
Reupload file repository 19 februari 2026_agus/feren
Keywords: speaking; junior high school